Behavior of smeared zone and performance of PVD improvement under vacuum preloading on soft Bangkok clay - Le Gia Lam; Bergado, Dennes T.; Park, Kyung Ho; Pham, Huy Giao; The Netherlands Government (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
This study presents the analytical and finite element simulations of reconstituted soil sample and natural ground improved with PVD only and combining PVD with vacuum and surcharge preloading. In the laboratory, large scale consolidometer tests of reconstituted Bangkok samples with size of 0.45 m in diameter and 0.78 m in height under surcharge and combining vacuum and surcharge were carried out. In case of PVD only, a surcharge of 100kPa was applied. The results showed that the settlements reached 91 % degree of consolidation corresponding to 113.9 mm within period of 47 days. In addition, in case of combining vacuum of -50 kPa and surcharge of 50 kPa, the result revealed that the measured settlement was 114.8 mm corresponding to 90% degree of consolidation within 42 days. In the field condition, two cases of PVD only improvement with embankment pre loading and two cases of PVD consolidation under combining embankment and vacuum preloading in Second Bangkok International Airport Project were considered. In case of improvement with embankment preloading only, PVDs were installed in square pattern with spacing of 1m and 10m in depth. Embankment was constructed up to 3.8m height and divided into 3 stages. Observed settlements of 1.434m and 1.447m were recorded with 369 days of consolidation at two locations. In the vacuum PVD improvement, combining the embankment height of 2.8m and vacuum pressure of -60kPa preloading were utilized. The PVDs were installed in triangular pattern with spacing of 0.85 m and depth of 10m. Observations showed that the settlements of 1.273m and 1.336m were obtained with 116days of consolidation. FEM simulations and back calculations revealed that PVD improvement with vacuum preloading is faster than that of normal PVD in the laboratory and field conditions due to the reduced effect of smeared zone and increased coefficient of consolidation during vacuum preloading
A thesis proposal submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Geotechnical and Geoenvironmental Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2009
Keywords: Vertical drains -- Thailand -- Bangkok; Clay -- Thailand -- Bangkok -- Analysis